The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3qi00180f
|View full text |Cite
|
Sign up to set email alerts
|

Site preference and defect engineering of a highly efficient blue-emitting phosphor Sr2SiO4:Ce3+/K+ toward thermally enhanced luminescence

Abstract: Blue-emitting phosphor is one of the trichromatic phosphors essential for the development of near-ultraviolet (nUV) pumped phosphor-converted white light-emitting diodes (pc-WLEDs). Efficiency and thermal stability are two critical factors for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The spectral change was observed by varying the excitation wavelength from 320 nm to 365 nm, suggesting that there are two luminescence centers of Eu 2+ in the phosphor, which correspond to the 10-fold coordinated Sr1 and 9-fold coordinated Sr2. 25 While applying Gaussian decomposition to the PL spectrum excited at 365 nm, two peaks at 20 789 cm −1 (481 nm) and 18 179 cm −1 (550 nm) can be well fitted (Fig. 2b).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The spectral change was observed by varying the excitation wavelength from 320 nm to 365 nm, suggesting that there are two luminescence centers of Eu 2+ in the phosphor, which correspond to the 10-fold coordinated Sr1 and 9-fold coordinated Sr2. 25 While applying Gaussian decomposition to the PL spectrum excited at 365 nm, two peaks at 20 789 cm −1 (481 nm) and 18 179 cm −1 (550 nm) can be well fitted (Fig. 2b).…”
Section: Resultsmentioning
confidence: 89%
“…Besides, our recent study illustrated that Ce 3+ activated α′-Sr 2 SiO 4 has thermally enhanced luminescence under the excitation of n-UV light. 25 In order to investigate the tunability of photoluminescence of α′-Sr 2 SiO 4 based phosphors co-activated by Ce 3+ /Eu 2+ , we adopted a fixed Eu 2+ concentration (0.01) and a range of Ce 3+ doping concentrations ( x , 0.01–0.035) in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Fig. 5d, the [N(CH 3 ) 4 ] 3 MoO 3 F 3 : Mn 4+ phosphor has significant thermal quenching behavior, and according to Arrhenius eqn (9), the activation energy (E a ) required for quenching the formation temperature of the sample is 0.27 eV: [50][51][52]…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Therefore, we believe that reducing the number of quenching centers (defects and impurities) or implementing new phase-building strategies will be necessary. Based on current research, unlike most ion-doped materials, 9,10 for Mn 4+ -doped phosphors, whether the matrix ions undergo equivalent substitution to form a solid solution system or non-equivalent substitution for charge compensation, the introduction of these ions can reduce the quenching centers and thus improve the optical properties of phosphors to varying degrees. For instance, Hong et al reported the formation of a solid solution through ion co-doping, which effectively enhanced the luminescence intensity, thermal stability and hydrophobic stability of the Na 2 SiF 6 :Mn 4+ phosphor.…”
Section: Introductionmentioning
confidence: 99%